AI-Based Cybersecurity System for 5G Enabled Mini Computers Running Pardus OS - Alsharif, F.; Basaran, E.C.; Agca, A.E.; Topcuoglu, E. (Institute of Electrical and Electronics Engineers Inc., 2025)
This paper presents an AI-driven cybersecurity system tailored for 5G-enabled mini computers running the Pardus operating system. The system integrates real-time network monitoring using Suricata with dynamic threat intelligence from the Open Threat Exchange (OTX), allowing for the automated blocking of globally recognized threats. Detection is performed through a two-stage Random Forest model trained on the 5G-NIDD dataset, where 24 features were mapped from Suricata's traffic output. The binary classification model achieved 99.78% accuracy in distinguishing benign from malicious traffic, while the multiclass model identified specific attack types-such as HTTPFlood, SYNScan, and UDPFlood-with 97.48% accuracy. Designed with the computational constraints of edge environments in mind, the system incorporates lightweight, high-precision AI models and rule-based response mechanisms capable of executing threat-specific countermeasures in real time. Evaluation on a 5G-enabled mini computer demonstrates that the proposed approach delivers reliable detection performance with low latency and minimal resource usage, making it a practical solution for industrial IoT, smart infrastructure, and mobile edge deployments where autonomous and adaptive cyber defense is critical. © 2025 IEEE.
Keywords: 5G Technology; AI-Based Cybersecurity; Autonomous Defense Mechanism; Mini Computers; Pardus OS; Threat Detection and Classification